Islamic Law Perspective on Settlement of Inheritance Disputes - Arsyam Arsyam; Siti Musyahidah; Malkan Malkan (State Institute for Islamic Studies Palu, 2021)
This study discusses the process of inheritance dispute resolution in the Religious Court of Palu City. This study is a literature review study. While the approach used in this study is a normative approach, which is based on the texts of the Qur'an, Al-Hadith and a juridical approach, which is based on the compilation of Islamic law and the Law of Religion Court authority. This research data analysis method uses an inductive pattern, which is an analysis that departs from concrete facts or events in the decisions of the Religious Courts even to the Supreme court then general conclusion was drawn. This research is descriptive-analytical in nature, namely research that seeks to describe the process of resolving inheritance disputes in the Palu city religious court . Then in the analysis, the researcher tried to find the Islamic law perspective on the settlement of inheritance disputes. The results showed that the process of inheritance dispute resolution is the same as other litigation processes through the stage of registration entered into the head of the court then the head of the court determines 3 judges in handling the case of inheritance dispute. The distribution of inheritance at the Palu Religious Court carried out through a consensus by going through several stages in the trial channel. In that stage, it included the Palu Religious Court, then appealed to the high court until the end of the case of inheritance reached the Supreme Court. This is done in order to maintain the mutual benefit of the family suing each other.